2020
DOI: 10.1002/nano.202000053
|View full text |Cite
|
Sign up to set email alerts
|

Quinoidal bisthienoisatin based semiconductors: Synthesis, characterization, and carrier transport property

Abstract: Novel quinoidal bisthienoisatin (QBTI) derivatives end‐capped with phenyl and thienyl groups were designed and synthesized. Single‐crystal X‐ray structure analysis of phenyl group flanked QBTI molecule confirmed that the quinoidal structure contributed to the high planarity of the molecular skeleton and the construction of one‐dimensional stacks. The quinoidal form of bisthienoisatin derivatives displayed ambipolar carrier transport properties with mobilities of approximately 10−4 cm2 V−1 s−1. Different flanki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have shown that delocalization of π-electrons would increases E HOMO . [46] Therefore, we ascribe the higher E HOMO of TQDPP relative to that of BQDPP to the more electron-rich end-groups and the more extensive π-electron delocalization in the former.…”
Section: Properties Of the Tqdpp Building Blockmentioning
confidence: 99%
“…Previous studies have shown that delocalization of π-electrons would increases E HOMO . [46] Therefore, we ascribe the higher E HOMO of TQDPP relative to that of BQDPP to the more electron-rich end-groups and the more extensive π-electron delocalization in the former.…”
Section: Properties Of the Tqdpp Building Blockmentioning
confidence: 99%